Apparent digestibility of amino acids in feedstuffs used in diets for the pacific white shrimp, Penaeus vannamei = Eficiencia digestiva aparente de aminoácidos en ingredientes utilizados en dietas para camarón blanco del pacífico, Penaeus vannamei - Villarreal Cavazos, David Alonso; Ricque Marie, Denis; Nieto López, Martha; Tapia Salazar, Mireya; Lemme, Andreas; Gamboa Delgado, Julián; Cruz Suárez, Lucia Elizabeth (Instituto de Investigaciones Oceanológicas de la Universidad Autónoma de Baja California, 2019)
Apparent digestibility coefficients (ADC) for dry matter, energy, crude protein (CP), and amino acids (AA) were evaluated for 4 feedstuffs used to feed juvenile white shrimp (Penaeus vannamei): fish meal (73.5% CP), potato protein concentrate (89.3% CP), brewer’s yeast (42.5% CP), and crustacean meal (47.2% CP). Experimental diets included 30% of the test ingredient and 69% of a commercial diet supplemented with 1% chromium oxide as inert marker. Amino acid contents in the ingredients, experimental diets, leached diets, and feces were analyzed by high-performance liquid chromatography. Nutrient loss in water was highest in the fishmeal diet (25%). The AA with the highest losses in water were lysine, methionine, and arginine (25%, 23%, and 21%, respectively). The ADC for dry matter oscillated between 79.2% and 90.6%, for CP between 78.1% and 91.8%, and for AA between 75.4% and 96.6%. In all cases the lower limit corresponded to the meal with potato protein concentrate and the upper limit to the crustacean meal. The ADC for energy fluctuated between 89.1% and 95.2%, with the lower limit for the crustacean meal and the upper limit for the meal with potato protein concentrate.